Hubungan Penggunaan Media Sosial dengan Perkembangan Usaha Kecil dan Menengah Kuliner Wilayah Solo Raya - Zahrah Lathifah; Djuara P. Lubis (Jurnal Komunikasi Pembangunan, 2018)
Promotion through Social Media is a way for culinary Small and Medium-sized Enterprises (SME) in Solo Raya area for expanding the product’s information so it can persuade consument’s buying decision. The purpose of this research is to identify the correlations between the use of social media as promotion media with business improvement. This research is using confidence sampling and Rank Spearman for the statistical test. The result from this research is some of respondents characteristic has no correlations with the used of media social as promotion media. The behavior of social media users variable has a strong positive correlations and significant with the used of social media as promotion media. The other result from this research is doing promotion through social media has a medium positive correlations and also significant with business improvement.